The construction of discursive difficulty: the circulation of, and resistance to, moral asymmetries in the public debate over the invasion of Iraq in 2003 - Burridge, Joseph David (2005)
This thesis examines the operation of morally asymmetrical distinctions in the discourse produced in advance of the invasion of Iraq in March 2003. It does not set out to explain the invasion's occurrence, but, based upon the analysis of media texts, parliamentary debates, and political speeches, focuses upon aspects of the processes of justification and criticism preceding invasion. It blends together aspects of the work of Michel Foucault and Niklas Luhmann, with insights drawn from various approaches to the analysis of discourse and communication, in pursuit of an understanding of how the discursive space available to contributors to debate is restricted. It pays close attention to the closely related processes of 'disclaiming' and 'ontological gerrymandering' - interventions which are concerned with controlling what is, and is not, the case - particularly in terms of the way that they are orientated towards controlling how the person making them is to be observed. It is argued that the circulation of the illegitimacy of various positions puts some contributors at risk of being observed according to the more negative side of a morally asymmetrical distinction. It is argued that this creates 'difficulty' for them, and incites their engagement in particular forms of discursive work in the attempt to avoid illegitimacy themselves. Close attention is paid to any observable regularities in the ways in which contributors attempted to avoid having their position associated with, amongst other things, 'anti-Americanism', 'appeasement', 'pacifism', 'warmongering', or a 'pro-Saddam' stance, all of which would threaten their legitimacy. A variety of techniques are identified, including the invocation of a contributor's history of positions (their 'communicative career'), as well as their use of their allegedly less legitimate context-specific allies as a contrastive foil, at the expense of whom they claim their own legitimacy.